3D non-linear finite element analysis of concentrically loaded high strength reinforced concrete column with GFRP bar - Adhi Dharma Prasetyo; Bambang Piscesa; Harun Alrasyid; Dwi Prasetya (Institut Teknologi Sepuluh Nopember (ITS), 2020)
The use of High Strength Concrete (HSC) material in Reinforced Concrete (RC) column has become widely used.HSC was found to be durable, strong in compression, but it has low ductility. This low ductility of HSC can be improved byproviding confinement. However, for HSC with concrete strength higher than 70 MPa, additional clause for confinement in ACI318-19 generates denser arrangement of transverse bars and eventually creates weak planes between the concrete core and thecover. These weak planes can trigger early cover spalling. To reduce the utilization of confining bars, high-strength Glass FiberReinforce Polymer (GFRP) bar can be used. However, the performance of GFRP bar varies significantly from their uniaxialbehavior in tension or compression to the real performance when it is used as the main reinforcement. For that reason, thispaper tries to investigate the behavior of HSC RC column with bars made of conventional steel rebar and with GFRP bars. Dueto limited data on the strain gauge reading on the GFRP bars from the available test result, an inverse analysis is carried outto determine the best stress-strain curve for GFRP bars used as the main reinforcement. For that purpose, an inhouse finiteelement package called 3D-NLFEA is used. From the comparisons, it was found out that the peak load, softening behavior, andthe concrete core enhancement prediction agrees well with the test result. From the inverse analysis, only 25% and 45% of theGFRP bar yield strength can be deployed when loaded under compression and tension, respectively.